Purely Organic Blue Room‐Temperature Phosphorescence Activated by Acrylamide In Situ Photopolymerization. Issue 22 (22nd August 2022) - Sun, Yonghui; Chen, Yong; Jiang, Linnan; Yu, Xiaoyong; Qin, Yuexiu; Wang, Shuaipeng; Liu, Yu
Abstract: Purely organic room‐temperature phosphorescence (RTP), especially blue phosphorescence, has aroused considerable attention in organic optoelectronic applications. Herein, a purely solid supramolecular assembly with blue phosphorescence is constructed by 6‐bromoisoquinoline‐modified β‐cyclodextrin (CD‐IQ ), acrylamide (AAm), and cucurbit[7]uril (CB[7]) based on in situ photopolymerization strategy, accompanied by blue RTP emission at 450 nm. The abundant hydrogen‐bonding network between the formed polyacrylamide matrix and the β‐CD effectively restricts the motion of the 6‐bromoisoquinoline chromophore and suppresses the nonradiative transition, realizing purely blue RTP emission. As compared with CD‐IQ ‐polymer, supramolecular assembly between CB[7] and CD‐IQ can improve the quantum yield and lifetime from the initial 25.5% and 238.47 ms to 49.41% and 268.9 ms, respectively, which is attributed to the confinement effect of the cucurbituril hydrophobic cavity, and can be further applied in fields of anti‐counterfeiting, information encryption, and writing. Abstract : A facile long‐lived room‐temperature phosphorescence system is developed through an in situ photopolymerization strategy based on acrylamide with 6‐bromoisoquinoline‐modified β‐cyclodextrin and macrocyclic compound cucurbit[7]uril. Impressively, the assembly shows efficient blue phosphorescence emission at 450 nm with a lifetime of up to 268.9 ms and a quantum yield of up to 49.41% under ambient conditions.